Donald MacJannet, then associated with Tufts Medical School, photographed with Herbert Lagler, member of the YMCA Prisoners of War Committee, ca. 1944 - Unknown (Tufts Archival Research Center, 2005)
8x10; taken from MS024/007-108#002 - "MacJannet Personal Photos"